Aerobic, resistance or combined training: A systematic review and meta-analysis of exercise to reduce cardiovascular risk in adults with metabolic syndrome. (July 2018) - Wewege, Michael A.; Thom, Jeanette M.; Rye, Kerry-Anne; Parmenter, Belinda J.
Abstract: Background and aims: Exercise is beneficial to individuals with metabolic syndrome (MetS). An understudied group, who represent the majority of the MetS population, are individuals who have not developed diabetes. This review examined aerobic, resistance and combined (aerobic + resistance) exercise for cardiovascular risk factors in MetS without diabetes. Methods: Eight electronic databases were searched up to September 2017 for randomised controlled trials >4 weeks in duration that compared an exercise intervention to the non-exercise control in MetS without diabetes. MetS criteria, cardiorespiratory fitness and cardiovascular risk factors were meta-analysed in a random effects model. Results: Eleven studies with 16 interventions were included (12 aerobic, 4 resistance). Aerobic exercise significantly improved waist circumference −3.4 cm ( p < 0.01), fasting glucose −0.15 mmol/L ( p = 0.03), high-density cholesterol 0.05 mmol/L ( p = 0.02), triglycerides −0.29 mmol/L ( p < 0.01), diastolic blood pressure −1.6 mmHg ( p = 0.01), and cardiorespiratory fitness 4.2 ml/kg/min ( p < 0.01), among other outcomes. No significant effects were determined following resistance exercise possibly due to limited data. Sub-analyses suggested that aerobic exercise progressed to vigorous intensity, and conducted 3 days/week for ≥12 weeks offered larger and more widespread improvements. Conclusions: Aerobic exercise following current guidelines offers widespread benefits to individuals with MetS without diabetes. More studies on resistance/combined exercise programs in MetS are required to improve the quality of evidence. Highlights: Aerobic exercise appears the most beneficial mode for individuals with metabolic syndrome without type 2 diabetes. Longer duration interventions and progression to higher intensities may enhance the benefits of aerobic exercise. Resistance and combined exercise are key areas for future research in metabolic syndrome to optimise exercise prescription principles.